2014
DOI: 10.3390/ijms15010850
|View full text |Cite
|
Sign up to set email alerts
|

Changing Microspatial Patterns of Sulfate-Reducing Microorganisms (SRM) during Cycling of Marine Stromatolite Mats

Abstract: Microspatial arrangements of sulfate-reducing microorganisms (SRM) in surface microbial mats (~1.5 mm) forming open marine stromatolites were investigated. Previous research revealed three different mat types associated with these stromatolites, each with a unique petrographic signature. Here we focused on comparing “non-lithifying” (Type-1) and “lithifying” (Type-2) mats. Our results revealed three major trends: (1) Molecular typing using the dsrA probe revealed a shift in the SRM community composition betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…These findings corroborate further the suggestion that there are anoxic/suboxic microniches at the surface of smooth mats 28 65 . It has been proposed that tightly regulated metabolisms – potentially mediated by quorum sensing – of microbial consortia such as cyanobacteria, sulfate reducers/sulfur oxidisers, and methanogens/methanotrophs, may create these oxic and anoxic zones at mat surfaces 66 .…”
Section: Discussionsupporting
confidence: 89%
“…These findings corroborate further the suggestion that there are anoxic/suboxic microniches at the surface of smooth mats 28 65 . It has been proposed that tightly regulated metabolisms – potentially mediated by quorum sensing – of microbial consortia such as cyanobacteria, sulfate reducers/sulfur oxidisers, and methanogens/methanotrophs, may create these oxic and anoxic zones at mat surfaces 66 .…”
Section: Discussionsupporting
confidence: 89%
“…Thus it is suggested that an anoxic niche exists in the surface mat matrix to protect SRB from oxidative stress. The distribution of SRB in microbial mats forming marine stromatolites in the Bahamas was mapped using Geographical Information Systems and concluded clusters of SRB were common in lithifying mats 50 . Furthermore, our data indicating a large portion of other anaerobic members at the surface oxygenated layer (e.g.…”
Section: Discussionmentioning
confidence: 99%